Análise do cardápio fornecido aos discentes do ensino fundamental do município de Coari (AM) - Oliveira, Rainara de Souza (Brasil, 2020)
This research aimed to perform the analysis of the menu provided to elementary school students from the Municipal and State education of the city of Coari (AM), comparing the data with the recommendations of the National School Feeding Program (PNAE). The data were obtained through the information from the menus and datasheets served in October of 2019 in Municipal and State elementary schools of the city of Coari. During the analysis of the data, it was found a high prevalence of inadequacies in the composition of the menu offered to the students as in the energy amount, as in the amount of macro and micronutrients. The inadequacy of the values found in the nutritional composition of the school menu is harmful and exposes the student to nutritional deficiencies, besides influencing the physical, intellectual, and mental development of students.